2018
DOI: 10.1186/s12888-018-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression symptoms and their associated factors in mild COPD patients from community settings, Shanghai, China: a cross-sectional study

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a serious disease frequently accompanied by anxiety and depression. Few studies have focused on anxiety and depression for mild COPD patients in China. This study aimed to assess the prevalence and associated factors for anxiety and depression among patients with mild COPD in urban communities.MethodsA cross-sectional survey of 275 mild COPD patients was conducted in 6 communities randomly sampled from Pudong New Area of Shanghai, China, in 2016. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 44 publications
3
37
0
9
Order By: Relevance
“…In a study by Xiao et al, it was reported that after adjustment for covariates, female patients were more likely to suffer from anxiety (aOR = 6.41, 95% CI: 1.73-23.80) than male patients. 19 Likewise, we found anxiety was associated with ethnicity (p=0.002), educational status (p=0.014), marital status (p=0.002) and occupational status (p=0.015) whereas depression was associated with marital status (p=0.001), working status (p=0.015) and smoking status (p=0.034). Balcells et al, 2010 also found that strong association between the working status and presence of anxiety.…”
Section: 2% Patients Presented With Complaints Ofmentioning
confidence: 64%
“…In a study by Xiao et al, it was reported that after adjustment for covariates, female patients were more likely to suffer from anxiety (aOR = 6.41, 95% CI: 1.73-23.80) than male patients. 19 Likewise, we found anxiety was associated with ethnicity (p=0.002), educational status (p=0.014), marital status (p=0.002) and occupational status (p=0.015) whereas depression was associated with marital status (p=0.001), working status (p=0.015) and smoking status (p=0.034). Balcells et al, 2010 also found that strong association between the working status and presence of anxiety.…”
Section: 2% Patients Presented With Complaints Ofmentioning
confidence: 64%
“…The reported prevalence of depression and anxiety are quite varied, depending on the population surveyed (smoking status, COPD severity) and the tools used for screening (43). For patients with stable COPD in primary care settings or respiratory clinics, the prevalence of depression varies widely from 10% to 57% (2,6), and for anxiety, prevalence ranges from 7% to 50% (2,5,6), with many of these patients being unaware of being affected by either condition (44).…”
Section: Prevalence Of Anxiety and Depression As Comorbidities In Chrmentioning
confidence: 99%
“…Risk factors for increased rates of depression include living alone (45) and gender. Females have a higher rate of both anxiety and depression (6,(46)(47)(48), and rates of depression have shown to correlate with severity of dyspnoea as compared with males (47), although the quality of life symptoms has not (18). Increasing severity of COPD is associated with higher rates of depression and anxiety (4,9,49); for example, in patients requiring long-term oxygen, 57%…”
Section: Prevalence Of Anxiety and Depression As Comorbidities In Chrmentioning
confidence: 99%
See 2 more Smart Citations